ANALYSIS OF MOTOR SKILLS OF ADOLESCENTS OF A SWIMMING TRAINING PROGRAM (Fiep Bulletin - online, 2015)
Total fitness refers to man's whole biopsychosocial side, that is, when one is ready for all biological, physical, psychological and social needs. Swimming is known as a sports activity, which can optimize motor development. Swimming involves motor, stabilizing and manipulative skills in aquatic environment and it's directly related to the compounds of motor fitness. Nineteen swimmers from both genders who had practiced for at least 6 months, 3 times a week were tested. Age of the subjects varied from 10 and 13.  It was conduct in a swimming school in Barra da Tijuca, Rio de Janeiro. Instruments used in this study were abdominal resistance test (AAHPER, 1976), long jump  test (JOHNSON; NELSON, 1979), grip (JOHNSON; NELSON, 1979), sit-and-reach test (JOHNSON; NELSON, 1979), Shuttle run and Tapping test based on the parameters of the EUROFIT TEST (1988) and the motor reaction velocity to a visual stimulus (REIS; GONÇALVES apud AMARAL, 2002).Results were analysed within inferential descriptive statistics, with mean values between ages and revealed that pre-adolescents and adolescents who were tested have motor according to normal parameters and above this, taking into consideration their training program. These results confirm the initial hypothesis once they reveal superiority in skills related to health and development of pre-adolescents and adolescents swimming practicers showing the influence of the swimming training on the motor skills.
Keywords: Motor skills; Swimming training; Adolescents